Uso de dispositivos móviles como recursos didácticos en Educación Secundaria: beneficios, desafíos y percepciones del profesorado (Praxis Educativa, 2026)
Information and Communication Technologies (ICT) have become one of the most widely used teaching tools in the field of education. This research project focuses on this area, with the main objective of analysing the potential benefits of mobile devices as digital teaching tools in secondary school classrooms. A quantitative and qualitative study was carried out, using a survey as a data collection tool. The sample consists of 45 teachers from public, private and state-subsidised secondary schools in the province of Alicante. The results show that teachers claim to be prepared and willing to use ICT in their subjects, but in most cases, students do not have the tools or sufficient skills to use them correctly in the classroom.
Keywords: ICT incorporation; Technology; Technological resources; Teacher training; Student development; Teaching innovation